1978
DOI: 10.1007/bf00224928
|View full text |Cite
|
Sign up to set email alerts
|

The cells of the rat gastric groove and cardia

Abstract: The distal wall of the groove between the rat forestomach and glandular stomach is lined with a special type of columnar cells (CCGG) and with fibrillovesicular cells (FVC). The cardiac glands contain cardiac mucosa (CMC) and serous cells (CSC). The CCGG contain small mucous granules and special vesicles and tubules. The CMC are filled with large mucous granules and resemble mucous neck cells. The CSC are filled with large proteinaceous granules. The FVC are characterized by long microvilli, apical bundles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

1979
1979
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…The weak supranuclear fluorescence seen in the brush all in b (right cell) results from a break through of the strong TRITC-fluorescence for CK-18 shown in a. Bar, 20 gm laments in brush cells has been repeatedly described at the ultrastructural level (Wattel and Geuze 1978;Luciano et al 1981;Gomi et al 1991). The present findings indicate that one major component of the intermediate filaments in brush cells is the basic cytokeratin type 18.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The weak supranuclear fluorescence seen in the brush all in b (right cell) results from a break through of the strong TRITC-fluorescence for CK-18 shown in a. Bar, 20 gm laments in brush cells has been repeatedly described at the ultrastructural level (Wattel and Geuze 1978;Luciano et al 1981;Gomi et al 1991). The present findings indicate that one major component of the intermediate filaments in brush cells is the basic cytokeratin type 18.…”
Section: Discussionmentioning
confidence: 81%
“…The strong apical tubulin immunostaining of brush cells was not observed in any other epithelial cell type of the gut and thus can be taken as a further cytological feature typical for brush cells. The close association between microtubules and vesicles of the tubulovesicular system (Nabeyama and Leblond 1974;Wattel and Geuze 1978;Tsubouchi and Leblond 1979;Trier et al 1987) suggests that the vesicles in brush cells might be linked and transported along microtubules. If microtubules in brush cells are also uniformly oriented in an apicobasal direction, as in the intestinal epithelium (Achler et al 1989), microtubules may be important for the vectorial delivery of these vesicles to the apical cell pole.…”
Section: Discussionmentioning
confidence: 97%
“…Binding of taste molecules to these receptors is thought to induce GTP binding to a-gustducin that, like other G,-proteins, stimulates second messenger systems involved in signal transduction. The lumenal cell pole of both brush cells (4,5,6,12) and taste receptor cells (11) contains numerous microvilli that are the most likely site for chemoreception. In support of this notion, we found that the lumenal cell pole of both cell types was the most strongly immunolabeled portion.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we addressed the question ofwhether the epithelium of the gut might express a-gustducin, the GTP-binding a-subunit of a trimeric Gprotein complex that is specific for taste receptor cells of the tongue (3). Here we show that a-gustducin is also expressed in the epithelium of the gut where it is associated with a specialized cell type long known under the names brush cell, tufted cell, or caveolated cell (4)(5)(6). The function of this cell type, which is present in humans, rats, and probably all other mammals, had been enigmatic until now.…”
mentioning
confidence: 82%
“…3) The mucus/ pepsinogen-secreting neck cells have been well characterized as an entity separate from zymogenic and pit cells by Wattel and Geuze (15). The mouse stomach contains 13 neck cells per unit; they are located in the neck region and their Golgi apparatus produces dense irregular material packed in the center of prosecretory vesicles and light material packed at the periphery of the same vesicles.…”
Section: Normal Micementioning
confidence: 99%